Elucidating the Role of RHT-1 Protein in Regulation of Gibberellin Signalling in the Aleurone of Wheat - Sokolowska, Patrycja (2021)
Germinating embryos release gibberellins (GAs), which act on aleurone cells to promote the expression of hydrolytic enzymes via the transcription factor (TF) GAMYB. GAs promote the degradation of DELLA proteins, which in the aleurone results in the upregulation of GAMYB expression. Although it is known that DELLAs negatively regulate GAMYB activity, the molecular mechanisms underlying this response are currently unclear. Recent studies have demonstrated that DELLAs do not contain a DNA-binding domain and they regulate transcription by acting as coactivators or corepressors of TFs. It was therefore hypothesised that the regulation of GAMYB by DELLA may be indirect, by working in a complex with other TF/TFs. A yeast two-hybrid (Y2H) screen of the wheat aleurone cDNA library revealed that wheat DELLA protein, RHT-1, interacts with different classes of TFs. Two TFs were selected for further analysis: INDETERMINATE DOMAIN 11 (TaIDD11) and ETHYLENE RESPONSE FACTOR 5 (TaERF5). The interactions between RHT-1 and TaIDD11 and TaERF5 were confirmed in Y2H assays and in planta. Reverse genetics approach was applied to understand the roles of identified TFs in the regulation of GA response. TaIDD11 was found to be a positive regulator of GA-mediated growth and floral transition, as the Taidd11 (triple knockout mutant) displayed reduced growth and delayed transition to flowering. The transcript levels of GA3ox, GA20ox and GID1b, the genes positively regulating GA biosynthesis and signalling, were enhanced in the mutant, which resulted in enhanced levels of bioactive GA1. The TaERF5 has a close paralogue in wheat (TaERF5a), which shows high level of conservation and is hypothesized to have redundant function. Genome editing using CRISPR/Cas9 was applied to generate sextuple Taerf5 Taerf5a mutant, and the Cas9-free T3 seeds are now awaiting phenotypic analysis. Together, this study identified a novel component of GA signalling that regulates GA-mediated growth and development, possibly via interaction with RHT-1.